Therapeutic gene editing in CD34+ hematopoietic progenitors from Fanconi anemia patients - Begoña Diez; Pietro Genovese; Francisco J Roman‐Rodriguez; Lara Alvarez; Giulia Schiroli; Laura Ugalde; Sandra Rodriguez‐Perales; Julian Sevilla; Cristina Diaz de Heredia; Michael C Holmes; Angelo Lombardo; Luigi Naldini; et al. (EMBO Molecular Medicine)
Abstract Gene targeting constitutes a new step in the development of gene therapy for inherited diseases. Although previous studies have shown the feasibility of editing fibroblasts from Fanconi anemia (FA) patients, here we aimed at conducting therapeutic gene editing in clinically relevant cells, such as hematopoietic stem cells (HSCs). In our first experiments, we showed that zinc finger nuclease (ZFN)‐mediated insertion of a non‐therapeutic EGFP‐reporter donor in the AAVS1 “safe harbor” locus of FA‐A lymphoblastic cell lines (LCLs), indicating that FANCA is not essential for the editing of human cells. When the same approach was conducted with therapeutic FANCA donors, an efficient phenotypic correction of FA‐A LCLs was obtained. Using primary cord blood CD34+ cells from healthy donors, gene targeting was confirmed not only in in vitro cultured cells, but also in hematopoietic precursors responsible for the repopulation of primary and secondary immunodeficient mice. Moreover, when similar experiments were conducted with mobilized peripheral blood CD34+ cells from FA‐A patients, we could demonstrate for the first time that gene targeting in primary hematopoietic precursors from FA patients is feasible and compatible with the phenotypic correction of these clinically relevant cells.